Investigation of the effects of antibiotic and single doses steroid application in cases of preterm premature rupture of membranes - Kumru, Selahattin; Gurates, Bilgin; Şimşek, Mehmet; Sapmaz, Ekrem; Parmaksiz, Cem; Aygün, Denizmen (My University, 2004)
PURPOSE: Investigation of the effects of antibiotic and steroid treatment on maternal and perinatal outcomes in preterm premature rupture of membranes (pPROM) cases. STUDY DESIGN: This study was undertaken in Firat University Medical School Department of Obstetric and Gynecology between January-December 2003. The study groups were consist of thirty three cases hospitalized and treated as pPROM. The patients in group I (n=16) were treated with antibiotic (ampicillin) alone, and the patients in group II were given single dose steroid (betamethasone) in addition to antibiotic. Maternal and perinatal outcomes were compared. RESULTS: Demographic characteristics of the study groups were similar. Latent periods elapsed from pPROM to delivery, the incidence of chorioamnionitis and endometritis were not different between two groups (p>0.05). Although, the incidences of respiratory distress syndrome were 18% in group I and 5% in group II this differences was not statistically significant (p>0.05). While isolette and newborn intensive care unit requirements were 43% vs. 23% and 23% vs. 12% in group I and group II, respectively; these findings were not different between two groups (p>0.05). CONCLUSION: Single dose steroid application together with antibiotic has no adverse effect on maternal and perinatal outcomes in cases of pPROM, produce a tendency reduced newborn morbidity.
Preterm erken membran rüptürü olgularinda antibiyotik tedavisi i?le birlikte tek doz steroid kullaniminin etkilerinin araştirilmasi
Keywords: Antibiotic; Preterm Premature Rupture of Membranes; Steroid